Inbred Rats as a Model to Study Persistent Renal Leptospirosis and Associated Cellular Immune Responsiveness - Nally, Jarlath E.; Wilson-Welder, Jennifer H.; Hornsby, Richard L.; Palmer, Mitchell V.; Alt, David P. (Frontiers in Cellular and Infection Microbiology, 2018)
Pathogenic species of Leptospira cause leptospirosis, a bacterial zoonotic disease with a global distribution affecting over one million people annually. Rats are regarded as one of the most significant reservoir hosts of infection for human disease, and in the absence of clinical signs of infection, excrete large numbers of organisms in their urine. A unique biological equilibrium exists between pathogenic leptospires and reservoir hosts of infection, but surprisingly, little is known concerning the host’s cellular immune response that facilitates persistent renal colonization. To address this deficiency, we established and applied an immunocompetent inbred rat model of persistent renal colonization; leptospires were detected in urine of experimentally infected rats by three weeks post-infection and remained positive until 8 weeks post-infection. However, there was little, if any, evidence of inflammation in colonized renal tubules. At eight weeks post-infection, a robust antibody response was detected against lipopolysaccharide and protein outer membrane (OM) components. Purified B and T cells derived from the spleen of infected and non-infected rats proliferated in response to stimulation with 0.5 µg of OM fractions of Leptospira, including CD4+ T cells, which comprised 40% of proliferating cells, compared to 25% in non-infected controls. However, analysis of gene expression did not determine which immunoregulatory pathways were activated. Lymphocytes purified from the lymph node draining the site of colonization, the renal lymph node, also showed an increase in percentage of proliferating B and T cells. However, in contrast to a phenotype of 40% CD4+ T cells in the spleen, the phenotype of proliferating T cells in the renal lymph node comprised 65% CD4+ T cells. These results confirm that the renal lymph node, the local lymphoid organ, is a dominant site containing Leptospira reactive CD4+ T cells and highlight the need to consider the local, versus systemic, immune responses during renal colonization infection. The use of inbred immunocompetent rats provides a novel tool to further elucidate those pathophysiological pathways that facilitate the unique biological equilibrium observed in reservoir hosts of leptospirosis.